Pengaruh Harga, Kualitas Produk, dan Online Customer Review Terhadap Minat Beli Konsumen pada Coffee Shop Bhineka Muda Denpasar - Gusdijaya Polos, Cakra; Ni Ketut Anjani (Jurnal of Management and Social Sciences, 2026)
This study shows that Coffee Shop Bhineka Muda Denpasar as one of the businesses in the culinary field faces quite tight competition with many new coffee shops emerging. This competition does not only occur in terms of price, but also in product quality, place concept, and presence in digital media. The population in this study was 975 people with a sample of 98 respondents, using Quantitative and Qualitative data types collected from primary and secondary sources both through documents, Questionnaires and the internet analyzed using Multiple linear regression analysis with the help of a computer using SPSS Version 26.0. The results of the study indicate that partially there is a positive and significant influence between the Price variable (X1), the Product Quality variable (X₂), the Online Customer Review variable (X₃) on Consumer Purchase Interest (Y) at Coffee Shop Bhineka Muda Denpasar. Simultaneously, there is a positive and significant influence between the Influence of Price (X₁), Product Quality (X₂) and Online Customer Review (X₃) on Consumer Purchase Interest (Y) at the Bhineka Muda Denpasar Coffee Shop. The Bhineka Muda Denpasar Coffee Shop is advised to implement an integrated marketing strategy by aligning competitive pricing, maintaining product quality consistency, and managing the reputation of online customer reviews simultaneously, because these three factors have been proven to have a positive and significant influence simultaneously on consumer purchase interest so that the combination of the three will have a maximum impact on increasing sales